Detection of single and multiple pregnancy depending on placentomes measurement in Shami goats in Iraq by Ultrasonography - Hussein, Khawla A. (The Iraqi Journal of Veterinary Medicine, 2018)
The aims of present study were designed to determine the relationship between fetal number single or twin and placentome measurement by real time Ultrasonography at different stage of pregnancy. Twenty mature female of shami goats were synchronized for estrus with vaginal sponges impregnated with 60 mg of medroxey progesterone acetate (MAP) (Esponja-vet – spanin) under strict hygienic conditions, the sponges were inserted by applicator for 14 days, following by eCG (Folligon) intra muscularly injection each female goats (doe) received 500 IU Folligon. At the time of sponges withdrawl, estrus detection was done and each doe expressed estrus sings serviced naturally by buck proven fertility to obtain pregnancy. Result showed 100% of female express estrus after synchronized Ultrasound examination was performed by trans-rectally with linear probe (7.5 and 5 MHz) in early stage of pregnancy and using sector probe (3.5MHz) to trans-abdominal examination, the examination of animal started done from day 30 to 100 post mating every 5 day. The placentome was observed at first time of pregnancy at day 30 by using trans rectal examination with liner probe as an echo-genic parts on the surface of endometerium. The study showed a significant effect (P≤0.05) in placentome growth and gestation age. The placentome diameter reached maximum size at days 91-100 and was 34.76 ± 0.41mm. Also the present study showed no significant differences between placentome diameter in single and twin pregnant doe at (P≤0.05). The average of placentome size in single and twin was respectively, 7.72 ±0.46 mm and 8.42±0.34 mm at day 30-41 of gestation, the measurements reached high value (34.76 ± 0.41 mm) at day 91-100 of pregnancy. In conclusion the detection of gestation age in Shami goats according to placentome measurement was not a reliable method after day 90-100 of gestation. Also the placentome diameter measurement is not a practical method for diagnosing fetal number (single, twin) in pregnant Shami does.